Ghostly Foundations:: Multicultural Space and Vancouver’s Chinatown in Sky Lee’s Disappearing Moon Cafe - Martin, Daniel (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2004)
Destabilizing official multiculturalism's assertion that there exists, in "heritage" sites such as Chinatown, an always present unity between the spatial present and the historical past, Sky Lee's Disappearing Moon Cafe refuses to let its own architectural centre represent Chinese-Canadian history and identity. Instead, Lee's characters drift within a spatial grid of knowledge constructed by the European imagination while, at the same time, disrupting any representation of an essential "Chineseness." Ultimately, the novel's consistent references to spectrality ensure an experience of "being with" ghosts: an experience of recuperating the past without succumbing to multicultural policy's insistence that ethnic histories function to sell spatial or architectural images of diversity and tolerance.